Inconsistencies in Terminology and Definitions of Organic Soil Materials. Issue 4 (18th July 2014) - Stolt, Mark H.; Bakken, Jonathan
Abstract : In the last several decades, soil scientists have been conducting studies of organic soil materials to address critical environmental issues such as sequestration of the greenhouse gas CO2 and identification of hydric soils for wetland delineation. These studies form the knowledge base that the larger scientific community relies on to provide an understanding of identifying hydric soils for wetland identification and metrics of soil C quantity, variability, and fluxes for global C studies and models. Critical to this knowledge base is a set of criteria, terms, and definitions that can be consistently applied within and across scientific disciplines. In this study, we examined the degree of decomposition of 84 organic soil horizons and discuss these data relative to the criteria for the sapric, hemic, and fibric decomposition classes. Of the 84 horizons analyzed, 68 met the laboratory pyrophosphate color requirement, but only 28 met the laboratory fiber content criteria suggesting some disconnect between rubbed fiber content and pyrophosphate color requirements. A review of the literature suggests that the application of the terms sapric, hemic, and fibric vary among soil standards and that although pyrophosphate color is required for determining decomposition class for classification of Histosols and many hydric soil indicators, few pedologists or wetland scientists use these data. The results from our study and review of selected standards regarding the definitions, terminology, and criteria used for the application and classification of organic soil materials suggest that the soil science community needs to be more consistent in how soil organic materials are defined.